Five rules of thumb for post-ELSI interdisciplinary collaborations. Issue 1 (2nd January 2016) - Balmer, Andrew S.; Calvert, Jane; Marris, Claire; Molyneux-Hodgson, Susan; Frow, Emma; Kearnes, Matthew; Bulpin, Kate; Schyfter, Pablo; Mackenzie, Adrian; Martin, Paul
ABSTRACT: In this paper we identify five rules of thumb for interdisciplinary collaboration across the natural and social sciences. We link these to efforts to move away from the 'ethical, legal and social issues' framework of interdisciplinarity and towards a post-ELSI collaborative space. It is in trying to open up such a space that we identify the need for: collaborative experimentation, taking risks, collaborative reflexivity, opening-up discussions of unshared goals and neighbourliness.